Systemic trust in Higher Education in South Africa: Policymaking during the COVID-19 pandemic - Lewin, Thandi; Parker, Diane (Critical Studies in Teaching and Learning, 2025)
This paper uses collaborative autoethnography and document analysis to examine the policymaking process during COVID-19 in the public higher education system in South Africa. The conceptual framework outlines the multi-dimensional nature of trust and the complexity of policy-making. The paper argues that system-wide cooperation was grounded in a form of systemic trust that was possible due to the nature of the COVID-19 emergency, the policy context of South African higher education, and interinstitutional relationships that had been built prior to the pandemic. We outline the nature of cooperation, enabling policy directions to be published quickly, supporting institutions to act flexibly within a legal framework that created conditions for the relatively safe completion of academic years. The paper argues that the systemic trust that existed during this time provides insights for the ways in which leadership and collaboration can create conditions for strengthening public trust in the system.